PENERAPAN MODEL PEMBELAJARAN THINK PAIR SHARE (TPS) UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS PESERTA DIDIK PADA PELAJARAN IPA - Hanafi, Jonari; Komalasari, Annisa (AL IBTIDAIYAH: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2025)
Critical thinking ability is an essential 21st century competency that is vital to be developed in the learning process, especially in Natural Sciences (IPA) subjects. Based on initial observations at MI Al-Inayah Pagerageung, it indicates that students' critical thinking abilities are still suboptimal, especially in solving problems that require high-level reasoning. This study aims to determine students' critical thinking abilities in Natural Sciences (IPA) subjects before and after using the Think Pair Share (TPS) learning model, as well as to determine the increase in students' critical thinking abilities in Natural Sciences (IPA) subjects between before and after using the Think Pair Share (TPS) learning model. The hypothesis in this study is that there is an increase in students' critical thinking abilities in Natural Sciences (IPA) subjects after the implementation of the Think Pair Share (TPS) learning model. This study uses a quantitative experimental method with a pre-experimental design of the one group pre-test-post-test type. The results of the study showed an increase in the average score from 28.76 in the pre-test with a low category to 58 in the post-test with a sufficient category. The t-test results showed that t count was 9.556, which was greater than t table of 1.694, which means Ha was accepted. It was concluded that there was an increase in students' critical thinking skills in Natural Science lessons after the implementation of the Think Pair Share (TPS) learning model.